Fraudulent Practices and the Implications for Corporate Accountability: A Qualitative Analysis at PT Tiga Pilar Sejahtera Food Tbk - Tyasningwuri, Elisabeth; Khoirunnisa, Isni; Salsabila, Nasywa; Fatin, Nadilla; Damayanti, Desi; Manurung, Herlina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This article was created by reviewing the case of fraudulent actions made by PT Tiga Pilar Sejahtera Food Tbk. The purpose of this article is to identify the problems of fraud in the preparation of financial statements at PT Tiga Pilar Sejahtera Food Tbk. The author uses the literature study method which involves reviewing and critically evaluating literature sources to understand and describe the latest research developments related to the topic taken. The result of this article is that the company was found to have manipulated the financial statements based on an investigation by Ernst & Young Indonesia (EY) in 2018 due to a significant decline in stock prices. The conclusion of this article is that PT Tiga Pilar Sejahtera Food Tbk is subject to imprisonment for 3 years, which is reduced by the defendant's detention period.